2013
DOI: 10.1080/13632752.2013.801112
|View full text |Cite
|
Sign up to set email alerts
|

Improving pupil referral unit outcomes: pupil perspectives

Abstract: Concern has been expressed about the quality of alternative provision for young people with social, emotional and behavioural difficulties, and the poor academic and social outcomes many experience. Little research has sought the views of the young people themselves regarding the enablers and barriers to positive outcomes they have encountered. A total of 16 semi-structured interviews were conducted with participants aged 12 to 16 years drawn from pupil referral units in two local authorities. Thematic analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…Whilst PRUs are not designed for (and should not be used as a destination for) vulnerable autistic children, it was seen to offer some protection from the sensory demands found in mainstream education (Lloyd & O'Regan, 1999;Michael & Frederickson, 2013). For autistic children, an inability to effectively digest the sensory environment may cause disruption to daily routines (Schaff, Toth-Cohen, Johnson, Outten, & Benevides, 2011) and lead to withdrawal or aggression (Bogdashina, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst PRUs are not designed for (and should not be used as a destination for) vulnerable autistic children, it was seen to offer some protection from the sensory demands found in mainstream education (Lloyd & O'Regan, 1999;Michael & Frederickson, 2013). For autistic children, an inability to effectively digest the sensory environment may cause disruption to daily routines (Schaff, Toth-Cohen, Johnson, Outten, & Benevides, 2011) and lead to withdrawal or aggression (Bogdashina, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Humphrey and Lewis (2008), for example, found that anxiety, sensory-sensitivities, bullying and low selfimage contributed to negative secondary school experiences in their sample of 20 autistic boys. More recently, Dillon, Underwood and Freemantle (2016) reported how 14 autistic secondary school students (11 boys, 3 girls) were positive about their environment and appreciated good relationships with staff; reiterating how calmer atmospheres and positive staff-pupil relationships are potentially crucial to inclusion (Brede et al, 2016;Lloyd & O'Regan, 1999;Makin, Hill & Pellicano, 2017;Michael & Frederickson, 2013;Robertson, Chamberlain, & Kasari, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herz and Haertel 2016), research specifically including students with SEBD and addressing their perspectives on social exclusion continues to be rare (Cefai and Cooper 2010;Michael and Frederickson 2013). Moreover, despite acknowledging that the views of students with SEBD are important, that they are experts on their own situation and can contribute to educational initiatives, policies and research which influence their education (Michael and Frederickson 2013;Rose and Asher 2004;Woodhead and Faulkner 2000), there is a lack of knowledge about the perspectives of primary school students with SEBD. Studies which do include the voices of young students with SEBD focus on the students' perspectives on the impact of inclusive education (Adderley et al 2015;Mowat 2015) or on the consequences of victimisation due to bullying (Brown Hajdukova, Hornby, and Cushman 2016;Messiou 2012), but have not yet considered what the students think about how social inclusion could be realised in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an increasing trend towards listening to student voices (e.g. Herz and Haertel 2016), research specifically including students with SEBD and addressing their perspectives on social exclusion continues to be rare (Cefai and Cooper 2010;Michael and Frederickson 2013). Moreover, despite acknowledging that the views of students with SEBD are important, that they are experts on their own situation and can contribute to educational initiatives, policies and research which influence their education (Michael and Frederickson 2013;Rose and Asher 2004;Woodhead and Faulkner 2000), there is a lack of knowledge about the perspectives of primary school students with SEBD.…”
Section: Introductionmentioning
confidence: 99%